2022
DOI: 10.1038/s41477-022-01255-2
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a K+ channel ‘sensory antenna’ enhances stomatal kinetics, water use efficiency and photosynthesis

Abstract: K + channel / ion channel clustering / channel gating, K + dependent / photosynthesis / stomatal gas exchange / Arabidopsis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…Values are steady-state means ± SE from n plants with individual measurements indicated by small symbols. Asterisks indicate significant differences (****p ≤ 0.0001) by post-hoc unpaired t test.from a conditioning voltage negative of E K to more positive values, yielded time-and voltage-dependent currents characteristic of outward-rectifying K + channels described previously(Blatt & Gradmann, 1997;Horaruang et al, 2022). As is typical of these channels, increasing external K + shifted the steady-state currentvoltage (I-V) curves to more positive voltages and slowed current activation at any one voltage (Figure4a,b).To assess the selectivity and [K + ] dependence of the channels, tail currents were analysed from G. gynandra guard cells by stepping to more negative voltages after activating the current.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Values are steady-state means ± SE from n plants with individual measurements indicated by small symbols. Asterisks indicate significant differences (****p ≤ 0.0001) by post-hoc unpaired t test.from a conditioning voltage negative of E K to more positive values, yielded time-and voltage-dependent currents characteristic of outward-rectifying K + channels described previously(Blatt & Gradmann, 1997;Horaruang et al, 2022). As is typical of these channels, increasing external K + shifted the steady-state currentvoltage (I-V) curves to more positive voltages and slowed current activation at any one voltage (Figure4a,b).To assess the selectivity and [K + ] dependence of the channels, tail currents were analysed from G. gynandra guard cells by stepping to more negative voltages after activating the current.…”
mentioning
confidence: 78%
“…where V 1/2 and δ values were derived from joint fittings of the I-V curves to the Boltzmann function (Figure 4, Table 3). The comparison shows that the energy required for gating of the G. gynandra channel systems platform OnGuard3 (Horaruang et al, 2022;Jezek et al, 2021;Wang, Hills, et al, 2014;Wang, Noguchi, et al, 2014) and experiments in vivo (Horaruang et al, 2022) It is worth noting that the differences in gating of the outwardrectifying channels of G. gynandra and Arabidopsis almost certainly dominate over any differences in current amplitudes (Table 3;…”
Section: G Gynandra Maintains Lower and Faster Stomata Conductance Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…How gating in GORK and its homologs is coupled with extracellular K + remains a matter of interest, not least because it is likely to underpin the rapid stomatal movements of many plants with C 4 photosynthesis ( Alvim 2022 ) and has implications for the channel protein dynamics ( Eisenach et al 2014 ). My laboratory recently found that manipulating this coupling yields substantial gains in both water use efficiency and photosynthetic carbon assimilation when light fluctuates, as it commonly does in the environment ( Blatt and Alvim 2022 ; Horaruang et al 2022 ).…”
Section: The Guard Cell Modelmentioning
confidence: 99%
“…Most recently, OnGuard3 was used to guide the engineering of a guard cell ion channel for improved WUE and biomass gains (Horaruang et al, 2022).…”
Section: Inside the Onguard3e Platformmentioning
confidence: 99%